Conventional and Novel Strategies for Cellulose Isolation from Nut Shells: A Review - Andrea Están; Mónica Umaña; Valeria S. Eim; Gabriela Clemente; Susana Simal (Molecules, 2025)
Nut by-products, particularly shells, are a globally abundant agricultural residue. Their widespread accumulation poses a serious environmental challenge. However, nut shells are of great interest due to their inherent lignocellulosic composition. For instance, they are rich in cellulose, a high-value biopolymer widely used in the production of bio-based materials. Therefore, this review critically analyses conventional and novel pre-treatment strategies for the extraction of cellulose from nut shells, emphasising the importance of optimising valorisation routes to minimise ecological impact. Various techniques—ranging from alkaline treatments to emerging approaches such as deep eutectic solvents and hydrothermal methods—have been examined and compared. The findings in cellulose purification through different strategies reveal that, while some methods are promising, others remain underexplored. Emphasis is placed on the necessity of comprehending the specific structural and chemical characteristics of each type of nut shell; as such, knowledge is fundamental to understanding the efficiency of the applied methods. This review highlights the growing interest in the valorisation of nut shell by-products as promising lignocellulosic resources of significant utility. Therefore, it also reveals the need for further research, focusing on process scalability, cost-efficiency, and environmental impact. Advancing in these areas is essential to enable the transition of nut shells from waste to a highly valuable resource.